SPORT ACCOMPANIMENT OF SELF DEFENSE PENCAK SILAT BANJAR RAGA INSANI CLUB AT ARA PAYUNG VILLAGE - Ratno, Puji; Fadli, Zen; Irwansyah, Irwansyah (Universitas Negeri Medan, 2019)
This community service activity is one form of the implementation of the Tri Dharma of Higher Education. This activity was carried out in order to help preserve the pencak silat banjar culture which is in the Village of Ara Payung. The main problem faced by partners is that in carrying out the training of pencak silat trainers, they do not yet have the ability to prepare training programs, variations in the practice of pencak silat in the art of motion are not many. And the lack of training facilities that exist in supporting a good training process, and supporting facilities. The output targets in this activity are: Trainers are able to make a good and correct training program in accordance with the rules of coaching. Availability of standard martial arts training facilities in accordance with the provisions. The method used to achieve the objectives of this activity is. Coaching clinic for the preparation of training programs for pencak silat coach, and mentoring for banjar pencak silat training. This service activity has resulted in an exercise program that is used in training at tha club, the trainer is able to arrange an exercise program that can be applied in training, increasing the variety of training in the Pencak Silat Raga Insani club. With the training and mentoring activities, the enthusiasm of the teenagers in the village of Ara Payung was higher in participating in the martial arts training in his village.Keywords: Instrument, Talent, Karate.